Personal tools

ListT done right

From HaskellWiki

(Difference between revisions)
Jump to: navigation, search
(typo, and include imports)
(A pure example where LiftT fails to preserve associativity (but [] is not commutative).)
 
(7 intermediate revisions by 5 users not shown)
Line 40: Line 40:
   
 
instance Functor m => Functor (ListT m) where
 
instance Functor m => Functor (ListT m) where
fmap f (ListT m) = ListT $ fmap (fmap f) m where
+
fmap f (ListT m) = ListT $ fmap (fmap f) m
   
 
instance Functor m => Functor (MList' m) where
 
instance Functor m => Functor (MList' m) where
Line 163: Line 163:
 
=== Grouping effects ===
 
=== Grouping effects ===
   
I didn't understand the statement "<hask>ListT m</hask> isn't always a monad", even
+
I didn't understand the statement "<hask>ListT m</hask> isn't always a monad", even after I understood why it is too strict. I found the answer in [http://web.cecs.pdx.edu/~mpj/pubs/composing.html Composing Monads]. It's in fact a direct consequence of the unnecessary strictness. <hask>ListT m</hask> is not associative (which is one of the monad laws), because grouping affects when side effects are run (which may in turn affect the answers). Consider
after I understood why it is too strict. I found the answer in
 
[http://www.cse.ogi.edu/~mpj/pubs/composing.html Composing Monads]. It's in
 
fact a direct consequence of the unnecessary strictness. <hask>ListT m</hask> is
 
not associative (which is one of the monad laws), because grouping affects
 
when side effects are run (which may in turn affect the answers). Consider
 
   
 
<haskell>
 
<haskell>
Line 201: Line 201:
   
 
t1 :: ListT IO ()
 
t1 :: ListT IO ()
t1 = (a `mplus` a >> b) >> c
+
t1 = ((a `mplus` a) >> b) >> c
   
 
t2 :: ListT IO ()
 
t2 :: ListT IO ()
t2 = a `mplus` a >> (b >> c)
+
t2 = (a `mplus` a) >> (b >> c)
 
</haskell>
 
</haskell>
   
Line 210: Line 210:
   
 
[[Roberto Zunino]]
 
[[Roberto Zunino]]
  +
  +
=== Order of <hask>ListT []</hask> ===
  +
  +
This is a simple example that doesn't use <hask>IO</hask>, only pure <hask>ListT []</hask>.
  +
<haskell>
  +
v :: Int -> ListT [] Int
  +
v 0 = ListT [[0, 1]]
  +
v 1 = ListT [[0], [1]]
  +
  +
main = do
  +
print $ runListT $ ((v >=> v) >=> v) 0
  +
-- = [[0,1,0,0,1],[0,1,1,0,1],[0,1,0,0],[0,1,0,1],[0,1,1,0],[0,1,1,1]]
  +
print $ runListT $ (v >=> (v >=> v)) 0
  +
-- = [[0,1,0,0,1],[0,1,0,0],[0,1,0,1],[0,1,1,0,1],[0,1,1,0],[0,1,1,1]]
  +
</haskell>
  +
  +
Clearly, <hask>ListT []</hask> fails to preserve the associativity monad law.
  +
  +
This example violates the requirement given in [http://hackage.haskell.org/packages/archive/mtl/latest/doc/html/Control-Monad-List.html the documentation] that the inner monad has to be commutative. However, all the preceding examples use <hask>IO</hask> which is neither commutative, so I suppose this example is valid at the end. Most likely, a proper implementation of <hask>ListT</hask> should not have such a requirement.
  +
  +
--[[User:Petr Pudlak|PetrP]] 19:15, 27 September 2012 (UTC)
   
 
== Relation to Nondet ==
 
== Relation to Nondet ==
Line 236: Line 257:
   
 
There's no particular reason why I used fmap, except that the page has the (unfortunate!) title "ListT Done Right", and having Functor superclass of Monad certainly is the right thing. But I agree, that mistake has long been done and I feel my half-hearted cure is worse than the disease. You can find an alternative, more concise definition of a ListT transformer based on even-style lists here: [[ListT done right alternative]]
 
There's no particular reason why I used fmap, except that the page has the (unfortunate!) title "ListT Done Right", and having Functor superclass of Monad certainly is the right thing. But I agree, that mistake has long been done and I feel my half-hearted cure is worse than the disease. You can find an alternative, more concise definition of a ListT transformer based on even-style lists here: [[ListT done right alternative]]
  +
  +
[[amb]] has AmbT, which could be considered as 'ListT done right' (since Amb is identical to the list monad).
   
 
[[Category:Monad]]
 
[[Category:Monad]]

Latest revision as of 19:15, 27 September 2012

Contents

[edit] 1 Introduction

The Haskell hierarchical libraries implement a ListT monad transformer. There are, however, some problems with that implementation.

  • ListT
    imposes unnecessary strictness.
  • ListT
    isn't really a monad transformer, ie.
    ListT m
    isn't always a monad for a monad
    m
    .

See the #Examples below for demonstrations of these problems.

[edit] 2 Implementation

The following implementation tries to provide a replacement for the ListT transformer using the following technique. Instead of associating a monadic side effect with a list of values (
m [a]
), it lets each element of the list have its own side effects, which only get `excecuted' if this element of the list is really inspected.

There is also a ListT done right alternative.

import Data.Maybe
import Control.Monad.State
import Control.Monad.Reader
import Control.Monad.Error
import Control.Monad.Cont
 
-- The monadic list type
data MList' m a = MNil | a `MCons` MList m a
type MList m a  = m (MList' m a)
 
-- This can be directly used as a monad transformer
newtype ListT m a = ListT { runListT :: MList m a }
 
-- A "lazy" run function, which only calculates the first solution.
runListT' :: Functor m => ListT m a -> m (Maybe (a, ListT m a))
runListT' (ListT m) = fmap g m where
  g MNil = Nothing
  g (x `MCons` xs) = Just (x, ListT xs)
 
-- In ListT from Control.Monad this one is the data constructor ListT, so sadly, this code can't be a drop-in replacement.
liftList :: Monad m => [a] -> ListT m a
liftList [] = ListT $ return MNil
liftList (x:xs) = ListT . return $ x `MCons` (runListT $ liftList xs)
 
instance Functor m => Functor (ListT m) where
  fmap f (ListT m) = ListT $ fmap (fmap f) m
 
instance Functor m => Functor (MList' m) where  
  fmap _ MNil = MNil
  fmap f (x `MCons` xs) = f x `MCons` fmap (fmap f) xs
 
-- Why on earth isn't Monad declared `class Functor m => Monad m'?
-- I assume that a monad is always a functor, so the contexts 
-- get a little larger than actually necessary
instance (Functor m, Monad m) => Monad (ListT m) where
  return x = ListT . return $ x `MCons` return MNil
  m >>= f = joinListT $ fmap f m
 
instance MonadTrans ListT where
  lift = ListT . liftM (`MCons` return MNil)
 
instance (Functor m, Monad m) => MonadPlus (ListT m) where
  mzero = liftList []
  (ListT xs) `mplus` (ListT ys) = ListT $ xs `mAppend` ys
 
-- Implemenation of join
joinListT :: (Functor m, Monad m) => ListT m (ListT m a) -> ListT m a
joinListT (ListT xss) = ListT . joinMList $ fmap (fmap runListT) xss
 
joinMList :: (Functor m, Monad m) => MList m (MList m a) -> MList m a
joinMList = (=<<) joinMList'
 
joinMList' :: (Functor m, Monad m) => MList' m (MList m a) -> MList m a
joinMList' MNil = return MNil
joinMList' (x `MCons` xs) = x `mAppend` joinMList xs
 
mAppend :: (Functor m, Monad m) => MList m a -> MList m a -> MList m a
mAppend xs ys = (`mAppend'` ys) =<< xs
 
mAppend' :: (Functor m, Monad m) => MList' m a -> MList m a -> MList m a
mAppend' MNil           ys = ys
mAppend' (x `MCons` xs) ys = return $ x `MCons` mAppend xs ys
 
-- These things typecheck, but I haven't made sure what they do is sensible.
-- (callCC almost certainly has to be changed in the same way as throwError)
instance (MonadIO m, Functor m) => MonadIO (ListT m) where
  liftIO = lift . liftIO
 
instance (MonadReader s m, Functor m) => MonadReader s (ListT m) where
  ask     = lift ask
  local f = ListT . local f . runListT
 
instance (MonadState s m, Functor m) => MonadState s (ListT m) where
  get = lift get
  put = lift . put
 
instance (MonadCont m, Functor m) => MonadCont (ListT m) where
  callCC f = ListT $
    callCC $ \c ->
      runListT . f $ \a -> 
        ListT . c $ a `MCons` return MNil
 
instance (MonadError e m, Functor m) => MonadError e (ListT m) where
  throwError       = lift . throwError
{- This (perhaps more straightforward) implementation has the disadvantage
   that it only catches errors that occur at the first position of the 
   list.
  m `catchError` h = ListT $ runListT m `catchError` \e -> runListT (h e)
-}
  -- This is better because errors are caught everywhere in the list.
  (m :: ListT m a) `catchError` h = ListT . deepCatch . runListT $ m 
      where
    deepCatch :: MList m a -> MList m a
    deepCatch ml = fmap deepCatch' ml `catchError` \e -> runListT (h e)
 
    deepCatch' :: MList' m a -> MList' m a
    deepCatch' MNil = MNil 
    deepCatch' (x `MCons` xs) = x `MCons` deepCatch xs

[edit] 3 Examples

Here are some examples that show why the old ListT is not right, and how to use the new ListT instead.

[edit] 3.1 Sum of squares

Here's a silly example how to use ListT. It checks if an
Int
n
is a sum of two squares. Each inspected possibility is printed, and if the number is indeed a sum of squares, another message is printed. Note that with our ListT, runMyTest only evaluates the side effects needed to find the first representation of
n
as a sum of squares, which would be impossible with the ListT implementation of
Control.Monad.List.ListT
.
myTest :: Int -> ListT IO (Int, Int)
myTest n = do
  let squares = liftList . takeWhile (<=n) $ map (^(2::Int)) [0..]
  x <- squares
  y <- squares
  lift $ print (x,y)
  guard $ x + y == n
  lift $ putStrLn "Sum of squares."
  return (x,y)
 
runMyTest :: Int -> IO (Int, Int)  
runMyTest = fmap (fst . fromJust) . runListT' . myTest
A little example session (
runMyTest'
is implemented in exactly the same way as
runMyTest
, but uses
Control.Monad.List.ListT
):
*Main> runMyTest 5
(0,0)
(0,1)
(0,4)
(1,0)
(1,1)
(1,4)
Sum of squares.
*Main> runMyTest' 5
(0,0)
(0,1)
(0,4)
(1,0)
(1,1)
(1,4)
Sum of squares.
(4,0)
(4,1)
Sum of squares.
(4,4)

[edit] 3.2 Grouping effects

I didn't understand the statement "
ListT m
isn't always a monad", even after I understood why it is too strict. I found the answer in Composing Monads. It's in fact a direct consequence of the unnecessary strictness.
ListT m
is not associative (which is one of the monad laws), because grouping affects when side effects are run (which may in turn affect the answers). Consider
import Control.Monad.List
import Data.IORef
 
test1 :: ListT IO Int
test1 = do
  r <- liftIO (newIORef 0)
  (next r `mplus` next r >> next r `mplus` next r) >> next r `mplus` next r
 
test2 :: ListT IO Int
test2 = do
  r <- liftIO (newIORef 0)
  next r `mplus` next r >> (next r `mplus` next r >> next r `mplus` next r)
 
next :: IORef Int -> ListT IO Int
next r = liftIO $ do  x <- readIORef r
                      writeIORef r (x+1)
                      return x

Under Control.Monad.List.ListT, test1 returns the answers

[6,7,8,9,10,11,12,13]
while test2 returns the answers
[4,5,6,7,10,11,12,13]
. Under the above ListT (if all answers are forced), both return
[2,3,5,6,9,10,12,13]
.

Andrew Pimlott

[edit] 3.3 Order of printing

Here is another (simpler?) example showing why "
ListT m
isn't always a monad".
a,b,c :: ListT IO ()
[a,b,c] = map (liftIO . putChar) ['a','b','c']
 
t1 :: ListT IO ()
t1 = ((a `mplus` a) >> b) >> c
 
t2 :: ListT IO ()
t2 = (a `mplus` a) >> (b >> c)
Under
Control.Monad.List.ListT
, running
runListT t1
prints "aabbcc", while
runListT t2
instead prints "aabcbc". Under the above ListT, they both print "abc" (if all answers were forced, they would print "abcabc").

Roberto Zunino

[edit] 3.4 Order of
ListT []

This is a simple example that doesn't use
IO
, only pure
ListT []
.
v :: Int -> ListT [] Int
v 0 = ListT [[0, 1]]
v 1 = ListT [[0], [1]]
 
main = do
    print $ runListT $ ((v >=> v) >=> v) 0
    -- = [[0,1,0,0,1],[0,1,1,0,1],[0,1,0,0],[0,1,0,1],[0,1,1,0],[0,1,1,1]]
    print $ runListT $ (v >=> (v >=> v)) 0
    -- = [[0,1,0,0,1],[0,1,0,0],[0,1,0,1],[0,1,1,0,1],[0,1,1,0],[0,1,1,1]]
Clearly,
ListT []
fails to preserve the associativity monad law. This example violates the requirement given in the documentation that the inner monad has to be commutative. However, all the preceding examples use
IO
which is neither commutative, so I suppose this example is valid at the end. Most likely, a proper implementation of
ListT
should not have such a requirement.

--PetrP 19:15, 27 September 2012 (UTC)

[edit] 4 Relation to Nondet

NonDeterminism describes another monad transformer that can also be used to model nondeterminism. In fact,
ListT
and
NondetT
are quite similar with the following two functions translating between them
toListT :: (Monad m) => NondetT m a -> ListT m a
toListT (NondetT fold) = ListT $ fold ((return.) . MCons) (return MNil)
 
toNondetT :: (Monad m) => ListT m a -> NondetT m a
toNondetT (ListT ml) = NondetT (\c n -> fold c n ml) where
  fold :: Monad m => (a -> m b -> m b) -> m b -> MList m a -> m b
  fold c n xs = fold' c n =<< xs
 
  fold' :: Monad m => (a -> m b -> m b) -> m b -> MList' m a -> m b
  fold' _ n MNil = n
  fold' c n (x `MCons` xs) = c x (fold c n xs)
ListT
is smaller than
NondetT
in the sense that
toListT . toNondetT
is the identity (is it ok to call
ListT
`retract'?). However, these functions don't define an isomorphism (check for example
NondetT (\_ n -> liftM2 const n n)
).

Thomas Jaeger

I propose to replace every occurence of `fmap` in the above code with `liftM`, thereby moving `class Functor` and the complaint about it not being a superclass of `Monad` completely out of the picture. I'd simply do it, if there wasn't this feeling that I have overlooked something obvious. What is it? -- Udo Stenzel

There's no particular reason why I used fmap, except that the page has the (unfortunate!) title "ListT Done Right", and having Functor superclass of Monad certainly is the right thing. But I agree, that mistake has long been done and I feel my half-hearted cure is worse than the disease. You can find an alternative, more concise definition of a ListT transformer based on even-style lists here: ListT done right alternative

amb has AmbT, which could be considered as 'ListT done right' (since Amb is identical to the list monad).